A Spectre is Haunting Swedish Archaeology – The Spectre of Politics: Archaeology, Cultural Heritage and the Present Political Situation in Sweden - Gustafsson , Anders; Karlsson , Håkan (Current Swedish Archaeology, 2011)
Today Swedish archaeology and cultural heritage management are embraced by the xenophobic party Sweden Democrats. This is a problematic situation, and once again it is therefore time to discuss the rela tionship between archaeology, cultural heritage and politics – not as a consequence of theoretical considera tions and standpoints, but against the background of the harsh political reality. The overall aim of this pa per is to contribute to the discussion concerning which strategy, or strategies, Swedish archaeology and cul tural heritage management should adopt as a response to the present political situation and as a defence of a solidaristic and multicultural Swedish society.